Lifts and service lifts Part 6. Code of practice for selection and installation (BSI, 1985)
Passenger lifts, Goods lifts, Service lifts, Lifts, Electrically-operated devices, Hydraulically-operated devices, Installation, Maintenance, Design, Dimensions, Construction works, Lift wells, Equipment housing facilities, Safety devices, Safety measures, Warning devices, Signs, Symbols, Velocity, Performance, Control systems, Velocity control, Emergency measures, Protective barriers, Machine guards, Electric motors, Induction motors